Effect of case-based learning in reproductive physiology on cognitive domain scores of first-year medical students in Western India - Bhattacharya, Srabani N.; Malgaonkar, Aniruddha A.; Kartikeyan, Sundaram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The Medical Council of India has recommended early clinical exposure, problem-oriented approach and case-based learning throughout the graduate medical curriculum. Case-based learning is a teaching-learning model that helps effective use of student and faculty time. Methods: This complete-enumeration, before-and-after type of educational intervention study (without controls) was conducted in a municipal medical college in Western India. After explaining the objectives of the study to first-year medical students, aged 18 years and above, of either sex, written informed consent was obtained from students (n=55) who were willing to participate in the study. The pre-test was conducted after lectures by faculty from the Departments of Physiology and Community Medicine. An identical post-test was administered after case-based learning, which was conducted by the same faculty in two sub-groups. The outcome studied was the difference in cognitive domain scores after attending lectures (by a pre-test) and case-based learning (by a post-test). Results: The overall mean score increased from 5.36 ± 0.97 (95% CI: 5.11 - 5.62) in the pre-test to 6.49 ± 1.14 (95% CI: 6.19 - 6.79) in the post-test. The differences between the pre- and post-test correct responses were statistically significant for two questions. Conclusions: The participating first-year medical students had adequate basic knowledge of reproductive physiology. Gender differences in correct responses were statistically significant for few questions. Use of case scenarios enhanced cognitive domain scores.